Frustration in Voyage Charters- Silted-up Backwater or Vital Navigation Resource? - Andrew Tettenborn (The Evolving Law and Practice of Voyage Charterparties, 2009)
The subject of frustration can throw up some surprisingly awkward (and at times unusually topical) problems in voyage charters.